Determinan Indeks Harga Saham Gabungan di Indonesia Periode 2000-2020 - Geovano Kamajaya, Davis; Perwithosuci, Winny (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
The Jakarta Composite Index (IHSG) is one of the stock market indices used by the Indonesia Stock Exchange (IDX). This index covers the price movements of all common and preferred stocks listed on the IDX. IHSG is of significant interest to all investors, as its movements influence whether investors will buy, hold, or sell their stocks. This study aims to estimate the impact of inflation, exchange rates, interest rates, and economic growth on IHSG for the period 2000-2020 using Ordinary Least Squares (OLS) regression analysis. The OLS method is a statistical technique used to identify the relationship between independent and dependent variables in a linear regression model. The results of the study indicate that exchange rates and economic growth have a positive impact on IHSG, while inflation negatively affects IHSG. Meanwhile, interest rates do not have an impact on IHSG. The government and Bank Indonesia, as the monetary authority in Indonesia, are expected to control inflation in order to stimulate the economy, encourage investor confidence, and foster the development of the capital market in Indonesia.